New feather mites of the genus Neodectes (Acariformes: Proctophyllodidae) from honeyeaters (Passeriformes: Meliphagidae) in Australia - Mironov, Sergey V.; Proctor, Heather C. (Zootaxa, 2023)
Five new species of the genus Neodectes Park and Atyeo, 1971 (Proctophyllodidae: Pterodectinae) are described from honeyeaters (Passeriformes: Meliphagidae) in Australia: Neodectes cissomelae sp. n. from Cissomela pectoralis (Gould) (type host) and Melithreptus gularis laetior Gould; N. hallidayi sp. n. from Anthochaera carunculata (Shaw) (type host) and A. chrysoptera (Latham); N. manorinae sp. n. from Manorina melanocephala (Latham); N. ophioglossus sp. n. from Conopophila rufogularis (Gould) (type host) and Lichmera indistincta (Vigors and Horsfield); and N. walteri sp. n. from Anthochaera phrygia (Shaw). A key to species and a world checklist to Neodectes species are provided for the first time. A new combination, Neodectes dicranochaetus (Gaud, 1968) comb. n., is proposed for Proterothrix dicranochaeta Gaud, 1968, which is transferred herein to the genus Neodectes from Proterothrix Gaud, 1968 (Proctophyllodidae).